Redefinition of the genus Bannapone and description of B. cryptica sp. nov. Hymenoptera: Formicidae: Amblyoponinae) - Eguchi, Katsuyuki; Viet, Bui Tuan; Yamane, Seiki; Terayama, Mamoru (Zootaxa, 2015)
The ant genus Bannapone was established by Xu in 2000 and has been recognized as one of the rarest ant genera in the world. In the course of our careful examination of Asian species of Stigmatomma, we have found that the following Stigmatomma species share a unique morphological characteristic in mandibular dentition with Bannapone mulanae and B. scrobiceps: Stigmatomma caliginosum (Onoyama, 1999), Stigmatomma fulvida (Terayama, 1987), S. pertinax (Baroni Urbani, 1978), S. zwaluwenburgi Williams, 1946 and an unnamed species “Stigmatomma sp. eg-3”. In the present paper, we redefine Bannapone, describe “Stigmatomma sp. eg-3” as a new species of Bannapone, and transfer S. caliginosum, S. fulvida, S. pertinax and S. zwaluwenburgi Williams, 1946 to Bannapone.